Studies on surface tension of 1, 8-diazabicyclo [5.4.0] undec-7-ene (DBU)-glycerol and CO2-DBU-glycerol solutions at temperatures from 288.1 K to 323.1 K. (October 2018) - Liu, Yingying; Lin, Si; Lu, Houfang; Liu, Changjun; Wu, Kejing; Liang, Bin
Highlights: Surface tensions of DBU-glycerol and CO2 -DBU-glycerol solutions were measured. The surface tension of CO2 -DBU-glycerol is higher than that of DBU-glycerol. Four models were compared to correlate and predict the surface tension of DBU-glycerol. Proportionality method estimates surface tension of CO2 -DBU-glycerol precisely. Abstract: 1, 8-diazabicyclo [5.4.0] undec-7-ene (DBU)-glycerol system is a potential chemical absorbent of CO2 . The surface tension of DBU-glycerol and CO2 -DBU-glycerol systems at temperatures from 288.1 K to 323.1 K were studied using the Wilhelmy-plate method. In both systems, the surface tension decreases with increasing temperature, and the surface tensions of the DBU-glycerol and CO2 -DBU-glycerol systems decrease by approximately 13–19% and 17–35%, respectively, over the measured temperature range. In the DBU-glycerol binary system, the surface tension decreases gradually with increasing DBU mole fraction. The excess surface tension was calculated and the concentration of DBU at the surface was found to be higher than that of the bulk. Four models (Redlich-Kister, FLW, WCH, and Jouyban-Acree method) were compared to model the surface tension of the DBU-glycerol system. The Kalies and proportionality methods were compared for modeling the surface tension of the CO2 -DBU-glycerol solution. It was found that when the mass content of CO2 ( ω CO2 ) based on the total mass of DBU and glycerol is less than 8%, the surface tension of CO2 -DBU-glycerol is higher (maximum 31.3%) than that of DBU-glycerol. The Jouyban-Acree method and proportionality method are the best for calculating the surface tension of DBU-glycerol and DBU-glycerol-CO2 mixtures, respectively. The average relative deviations in the Jouyban-Acree and the proposed proportionality methods are 0.98% and 2.06%, respectively. Surface tension data can provide basic and useful information in the design of absorption equipment and subsequent operation for CO2 capture with DBU-glycerol solvent.